51.2k views
0 votes
What is the quotient of (x3 - 3x2 + 5x – 3) = (x - 1)?

x2 - 2x - 3
x2 + 2x + 7
x2-3x + 8
x2 - 2x + 3

2 Answers

4 votes

Answer:

D

Explanation:

User Jettina
by
6.3k points
1 vote

Note: Consider "÷" sign instead of "=".

Given:


(x^3-3x^2+5x-3)/ (x-1)

To find:

The quotient.

Solution:

We have,


(x^3-3x^2+5x-3)/ (x-1)

It can be written as


=(x^3-3x^2+5x-3)/(x-1)

Splitting the middle terms, we get


=(x^3-x^2-2x^2+2x+3x-3)/(x-1)


=(x^2(x-1)-2x(x-1)+3(x-1))/(x-1)

Taking out the common factor (x-1), we get


=((x-1)(x^2-2x+3))/(x-1)

Cancel the common factors.


=x^2-2x+3

The quotient is
x^2-2x+3.

Therefore, the correct option is D.

User Awalias
by
5.9k points